Understanding the Barriers to Exclusive Breastfeeding Among Urban Indonesian Mothers - Irmawati Irmawati; Mohammad Zen Rahfiludin; Zefan Adiputra Golo; Adhani Windari; Malihah Ramadhani Rum; Risky Kusuma Hartono (Faculty of Public Health, Hasanuddin University, Makassar, 2025)
Despite WHO recommendations advocating for Exclusive Breastfeeding (EBF) for the initial six months, EBF rates remain low in many countries, including Indonesia. This study identifies psychosocial, socioeconomic, and demographic factors influencing EBF practices in Semarang City. Methods: A quasi-experimental design involved 157 participants (98 mother-infant pairs and 49 peers) recruited from various public health centres from December 2023 to June 2024. The Kaplan-Meier survival curve, in conjunction with the log-rank test, was employed to assess the disparities in survival and the observed practices of EBF. The determinants of EBF duration were found using the cox proportional hazard ratio. Results: The mean duration of EBF was 18 weeks, a number of 33.7% of mothers did not complete full six months. Key findings reveal that peer support, maternal knowledge, attitudes, skills, education level, and employment status significantly influence EBF duration. Mothers who received peer support had greater EBF resilience compared to those who did not received peer support (HR 0,32, CI:0.197,0.528). Practical skill, favourable attitudes, and high knowledge were also important indicators of sustained EBF. Conversely, being a working mother and having lower education level increased the risk of early EBF cessation. Conclusions: The results emphasize the necessity of focused, context-specific interventions to promote EBF in urban areas. These insights carry implications for policy and program development aimed to enhance health consequences for mother and children. Further research in diverse socio-demographic contexts is recommended to better understand and support effective EBF practices.